Perancangan dan Pembuatan Prototype Sistem Pemadaman Api Otomatis Berbasis Mikrokontroler Pada Ruang Baterai Bus Listrik - hendrik setiawan; Sigit Iswahyudi; Sigit Joko Purnomo (P3M Politeknik Negeri Jember, 2026)
This study aims to design and develop a prototype of a fire suppression system for electric bus bateery compartments to mitigate the risk of thermal runway, shich can lead to catastrophic battery fires. The desin integrates an Arduino uno base controller eith themal and MQ-2 smoke sensors, connected to a fire suppression installation utilizing dry powder as the extinguishing agent. Testing results demonstrate that the system operates responsively and systematically the cooling fa activates 40℃ for thermal management, while the emergency fire suppression via a solenoid valve triggers automatically when the temperature reaches 60℃ or smoke density hits 200 ppm. The primary advantage of this prototype lies in its multi layered protection, combining proactive battery temperature conditioning with an automated fire extinguishing mechanism. This system significantly enhances the operational safety standards for electric vehicles by providing a reliable defense against battery relates hazards.